Cell signaling and cytomegalovirus reactivation: what do Src family kinases have to do with it?. (20th April 2020) - Reeves, Matthew B.
Abstract : Primary infection with human cytomegalovirus (HCMV) is usually asymptomatic and leads to the establishment of lifelong latent infection. A major site of latency are the CD34+ hematopoietic progenitor cells. Importantly, normal cellular differentiation of CD34+ cells to a macrophage or dendritic cell phenotype is concomitant with viral reactivation. Molecular studies of HCMV latency have shown that the latent viral genome is associated with histone proteins and that specific post-translational modifications of these histones correlates with the transcriptional activity of the genome arguing that expression of key viral genes that dictate latency and reactivation are subject to the rules of the histone code hypothesis postulated for the regulation of eukaryotic gene expression. Finally, many studies now point to a key role for multiple signaling pathways to provide the cue for HCMV reactivation. The challenge now is to understand the complex interplay between cell identity, transcriptional regulation and cell signaling that occurs to promote reactivation and, additionally, how HCMV may further manipulate these events to support reactivation. Understanding how HCMV utilizes these pathways to drive HCMV reactivation will provide new insight into the mechanisms that govern viral and host gene expression and, potentially, illuminate new, host-directed, therapeutic opportunities to support our attempts to control this important medical pathogen of immune-compromised individuals.